Pengaruh Struktur Modal Terhadap PPh Badan Terutang Pada Perusahaan Perkebunan Sawit Yang Terdaftar Bursa Efek Indonesia (BEI) Tahun 2020-2022 - Sonia Rianti; Ferdyan Wana Saputra; Niken Ayuningrum (Journal of Applied Accounting And Business, 2024)
Based on the background description above, the formulation of this research problem is whether the Long-term Debt to Asset Ratio (LDAR) and Debt to Equity Ratio (DER), when combined, have an influence on the Corporate Income Tax payable to palm oil plantation companies listed on the Indonesia Stock Exchange (BEI). ) The aim of this is whether the Long-term Debt to Asset Ratio (LDAR) and Debt to Equity Ratio (DER), when combined, have an influence on the Corporate Income Tax payable on plantation companies listed on the Indonesia Stock Exchange (BEI). Data collection techniques are steps that The most important thing in the research process, because the main goal of research is to obtain data. The data collection technique needed here is which data collection technique is most appropriate, so that valid and reliable data is obtained. the 2020-2022 period that met the sampling criteria. The data analysis method used in this research uses descriptive statistical tests.